Patient-Centered Medicine: A Necessary Condition for the Management of Functional Somatic Syndromes and Bodily Distress - Cathébras, Pascal (Frontiers in Medicine, 2021)
This paper argues that “functional”, “medically unexplained”, or “somatoform” symptoms and disorders necessarily require a patient-centered approach from the clinicians. In the first part I address the multiple causes of the patients’ suffering and I analyze the unease of the doctors faced with these disorders. I emphasize the iatrogenic role of medical investigations and the frequent failure in attempting to reassure the patients. I stress the difficulties in finding the right terms and concepts, despite overabundant nosological categories, to give a full account of psychosomatic complexity. Finally, I discuss the moral dimension attached to assigning a symptom, at times arbitrarily, to a psychogenic origin. The following part presents a brief reminder of the patient-centered approach (PCA) in medicine. In the last part, I aim to explain why and how patient-centered medicine should be applied in the context of functional disorders. First, because PCA focuses on the patients’ experience of illness rather than the disease from the medical point of view, which is, indeed, absent. Second, because PCA is the only way to avoid sterile attribution conflicts. Last, because PCA allows doctors and patients to collaboratively create plausible and non-stigmatizing explanations for the symptoms, which paves the way towards effective management.